Case Report: Optic Atrophy and Nephropathy With m.13513G>A/MT-ND5 mtDNA Pathogenic Variant - Barone, Valentina; La Morgia, Chiara; Caporali, Leonardo; Fiorini, Claudio; Carbonelli, Michele; Gramegna, Laura Ludovica; Bartiromo, Fiorina; Tonon, Caterina; Morandi, Luca; Liguori, Rocco; Petrini, Aurelia; Brugnano, Rachele; et al. (Frontiers in Genetics, 2022)
Isolated complex I deficiency represents the most common mitochondrial respiratory chain defect involved in mitochondrial disorders. Among these, the mitochondrial DNA (mtDNA) m.13513G>A pathogenic variant in the NADH dehydrogenase 5 subunit gene (MT-ND5) has been associated with heterogeneous manifestations, including phenotypic overlaps of Mitochondrial Encephalomyopathy with Lactic Acidosis and Stroke-like episodes, Leigh syndrome and Leber’s Hereditary Optic Neuropathy (LHON). Interestingly, this specific mutation has been recently described in patients with adult-onset nephropathy. We here report the unique combination of LHON, nephropathy, sensorineural deafness and subcortical and cerebellar atrophy in association with the m.13513G>A variant.